Incorporation of 1-methylcyclopropene and salicylic acid improves quality and shelf life of winter jujube (Zizyphus jujuba Mill. cv. Dongzao) through regulating reactive oxygen species metabolism - Zhang, Weida; Kang, Jiawei; Yang, Wanting; Guo, Huijing; Guo, Minrui; Chen, Guogang (Frontiers in Nutrition, 2022)
Winter jujube fruit is susceptible to aging, peel reddening, dehydration, shrinkage, and tissue softening during shelf life after it is removed from the cold storage conditions. In this study, the effects of 1-methylcyclopropene (1-MCP) and salicylic acid (SA) on the quality of winter jujube fruit during shelf life were investigated by measuring physiological indexes and the activities of antioxidant enzymes and enzymes related to reactive oxygen species (ROS) metabolism of winter jujube fruit. The results showed that 1-MCP treatment and SA treatment suppressed weight loss, respiratory rate, malondialdehyde (MDA) content, H2O2 content, and O2-· production rate, but improved firmness, color difference (ΔE), soluble solid content (SSC), titratable acidity (TA), superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), ascorbate peroxidase (APX), glutathione reductase (GR), phenylalanine ammonia-lyase (PAL) activities, ascorbic acid content, glutathione content, total phenolic content, and total flavonoid content in comparison with the control. Particularly, the combined treatment of 1-MCP and SA (1-MCP+SA treatment) showed the maximum efficacy compared to the 1-MCP treatment and SA treatment alone. 1-MCP+SA treatment exhibited the best preservation effect, followed by SA treatment and 1-MCP treatment. Thus, the combined treatment of 1-MCP and SA is an effective approach to maintain the postharvest quality of winter jujube fruit and extend the shelf life.